Manufacturing method of sliding electrode
By smoothing and selectively corroding the cemented carbide surface of sliding electrodes to prevent direct contact with the metal wire, the method enhances electrode longevity and reduces wear, facilitating continuous operation and cost savings.
Patent Information
- Application Number
- JP2022066424
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-04-13
AI Technical Summary
The lifespan of sliding electrodes in wire electrical discharge machines is limited due to wear and tear during electrical machining, leading to frequent position shifts and replacements, which disrupts continuous operation and increases costs.
A method involving lapping treatment to smooth the cemented carbide surface of sliding electrodes, followed by selective corrosion to remove the metal binder phase, ensuring it does not contact the conductive metal wire, and using characteristic X-ray analysis to calculate the corrosion depth accurately.
This method extends the service life of sliding electrodes by reducing wear, allowing for longer continuous operation without frequent position shifts or replacements, thereby lowering operational costs.
Smart Images

Figure 0007603323000004 
Figure 0007603323000005 
Figure 0007603323000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a sliding electrode of a conductive metal wire, which enables a longer life. [Background technology]
[0002] One of the industrial applications of conductive metal wires is wire electric discharge machining, a machining method that cuts materials using the heat of wire discharge. The wire, which is insulated in a liquid environment, is brought close to the workpiece, and a pulse current flows through it, raising the temperature to several thousand degrees Celsius, melting the workpiece and cutting it into the desired shape.
[0003] The wire EDM process is shown in a schematic diagram in Figure 1. Two sliding electrodes 1 are provided spaced apart in the vertical direction, and the sliding electrodes 1 are connected to a power supply 2. A conductive metal wire 3 used in a wire EDM machine is brought into contact with the sliding electrode 1, and the conductive metal wire 3 is moved continuously at a desired speed in one direction as indicated by the arrow in Figure 1.
[0004] The conductive metal wire 3 used in this wire EDM process is made of a copper alloy or molybdenum alloy wire, and passes in front of the part to be cut at a constant speed under a constant tension. Electric current is supplied by contacting the high-voltage sliding electrodes 1 installed above and below the workpiece. When the conductive metal wire 3, which is always under tension, passes over the sliding electrodes, a microscopically small gap is constantly created, making it easier for discharge to occur.
[0005] In this environment, the wire passage area of the sliding electrode 1 gradually wears away due to sliding and discharge, forming a groove-like depression.Continued use of this area thereafter increases the risk of the wire breaking, so when the depression deepens to a certain depth, it is determined that the wire has reached the end of its life, and the electrode is shifted or replaced to pass over a new smooth surface, power supply is resumed, and machining continues.
[0006] As a material for sliding electrodes in such operating environments, cemented carbide consisting of hard particles mainly made of tungsten carbide, which has excellent wear resistance and heat resistance, and a metallic bonding phase mainly made of Co or Ni, has been used.
[0007] In recent years, as workpieces have become larger and unmanned continuous operation has become more common, the lifespan of the sliding electrode in wire EDM machines has become an issue. The less work required to shift the electrode position or replace the electrode itself, the longer continuous operation is possible and the lower the cost can be, so there is a demand for a method to achieve a longer lifespan.
[0008] As an example of measures to improve the life of such sliding electrodes, as disclosed in Patent Document 1, efforts have been made to improve the wear resistance and heat resistance by adjusting the particle size of the hard particles and the phase ratio and composition of the metallic bonding phase. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2003-266243 A Summary of the Invention [Problem to be solved by the invention]
[0010] In the past, with regard to the phenomenon whereby the sliding electrode of a wire EDM machine wears out during electric current machining, forming dents and ultimately reaching the end of its life, adjustment of the particle size of the hard particles in the cemented carbide and adjustment of the phase ratio and composition of the metallic bonding phase have been studied, as mentioned above; however, sufficient research has not been conducted to understand the actual mechanism by which the dents form.
[0011] Regarding the wear phenomenon of the sliding electrode which constantly supplies current at high voltage, although it is an environment in which sliding with the metal wire occurs, the pressing force is much gentler than the high-speed, high-pressure sliding that a cemented carbide die experiences during the drawing process of a metal wire, the inventors conducted their study focusing on the discharge phenomenon.
[0012] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for manufacturing a sliding electrode of a conductive metal wire which suppresses the occurrence of wear during electric current processing and enables a longer service life. [Means for solving the problem]
[0013] In order to solve the above problems, the present invention provides a method for manufacturing a sliding electrode made of a cemented carbide containing a hard particle phase and a metallic bonding phase and used in wire electric discharge machining using a conductive metal wire, characterized in that a lapping treatment is performed on the cemented carbide surface in a final finishing step of a smoothing process before use. The surface roughness of the cemented carbide surface after this lapping treatment is preferably 0.01 μm or less in terms of Ra.
[0014] In the present invention, it is preferable to selectively etch only the metallic bonding phase on the surface of the cemented carbide so that the metallic bonding phase does not come into direct contact with the conductive metal wire.
[0015] This makes it possible to suppress wear during electric current machining and extend the tool life, reducing the need to shift the electrode position or replace the electrode itself, enabling continuous operation for long periods of time.
[0016] In addition, in the present invention, the depletion depth of the metallic bonding phase when only the metallic bonding phase is selectively etched can be calculated from four pieces of information: the composition of the cemented carbide base, the composition measured by characteristic X-ray analysis from the top surface after the cemented carbide base is processed into a sliding electrode and the metallic bonding phase is selectively etched, the composition of the metallic bonding phase remaining slightly between the hard particles in the depleted region of the selectively etched metallic bonding phase, and the analysis depth measured by the emission of characteristic X-rays in the characteristic X-ray analysis.
[0017] As a result, in the depletion zone after selective corrosion, a small amount of metallic bonding phase remains between the hard particles, and it becomes possible to efficiently calculate the amount of metallic bonding phase that changes smoothly at the interface, and to accurately calculate the corrosion depth in a non-destructive manner. Note that, from the viewpoint of strength retention, the selective corrosion depth is premised on being approximately the same as the average grain size of the hard particles. Effect of the Invention
[0018] According to the present invention, it is possible to manufacture a sliding electrode of a conductive metal wire that can suppress the occurrence of wear during electric current machining and can extend the life of the electrode. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic diagram showing a wire electric discharge machining process. [Diagram 2] FIG. 2 shows a smooth surface after polishing and a surface after selective etching of the metallic bonding phase. [Diagram 3] FIG. 1 is a schematic diagram showing a cross section of a cemented carbide tool after selective etching of the metallic bonding phase, and the change in the amount of CO, which is the main component of the metallic bonding phase, during the selective etching. [Figure 4] FIG. 2 is a diagram for defining the depletion depth of a metallic bonding phase. [Diagram 5] 1 is a flow chart of a method for measuring the depletion depth of a surface metal binder phase in a cemented carbide. [Figure 6] This is an image of the surface of a cemented carbide alloy taken with a scanning electron microscope. [Figure 7] FIG. 11 is a diagram showing test results of a discharge withstand voltage test. [Figure 8] FIG. 11 is a diagram showing test results of a discharge withstand voltage test. [Figure 9] FIG. 1 is a diagram showing the amount of wear of a sliding electrode in terms of cross-sectional area due to wear, depending on whether or not the surface of a cemented carbide alloy is subjected to selective etching treatment. [Figure 10] FIG. 13 is a diagram showing test results regarding the wear cross-sectional area. [Figure 11] FIG. 13 is a diagram showing test results regarding the wear cross-sectional area. [Figure 12]FIG. 2 is a schematic diagram showing the contact state between a conductive metal wire and a sliding electrode in a test regarding a wear cross-sectional area. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, a method for manufacturing a sliding electrode according to the present invention will be described based on an embodiment thereof. The method for manufacturing a sliding electrode of the present invention is a method for manufacturing a sliding electrode composed of a cemented carbide containing a hard particle phase and a metallic bonding phase, and used in wire electric discharge machining with a conductive metal wire, in which a lapping treatment is performed on the cemented carbide surface in the final finishing step of the smoothing process before use, and selectively corrodes only the metallic bonding phase on the surface of the cemented carbide, resulting in a structure in which the metallic bonding phase does not come into direct contact with the conductive metal wire.
[0021] Here, lapping is a polishing method in which a lapping agent, a mixture of abrasive grains, oil, etc., is placed between the tool and the surface of the workpiece, and the two are pressed together with an appropriate pressure while being moved relative to each other, removing a small amount of material from the surface of the workpiece with the lapping agent, thereby obtaining a smooth, finished surface with good dimensional accuracy. When carrying out this lapping, it is preferable that the surface roughness of the cemented carbide surface after lapping is 0.01 μm or less in terms of Ra.
[0022] 2 shows a smooth surface 4 after polishing and a surface 5 after selective etching of the metallic bonding phase 7. In the contact area between the hard particles 6, the metallic bonding phase 8 remains. A method for calculating the corrosion depth in the selective corrosion of the metallic bonding phase will be described below.
[0023] Figure 3 shows the cross section of the metallic bonding phase on the surface of a cemented carbide tool after selective etching and the C, the main component of the metallic bonding phase, O The graph shows the change in the amount of C in the depleted zone after selective corrosion. O The amount of C does not become completely zero, but fluctuates. From the area where the metallic bonding phase has been removed by corrosion, the amount of C in the unreacted area changes gradually. OA transition in quantity is occurring and the depletion depth needs to be defined in this region.
[0024] Therefore, the inventors assumed a linear change in composition as shown in FIG. 4 and defined the depletion depth of the metallic bonding phase. O The amount is m1, and the small amount of C remaining between the hard particles O Assume that the amount is m2, m2 and m1 are constant values, and the transition from m2 to m1 is a linear change, as shown in FIG.
[0025] This linear change occurs at C O The transition position of the amount of Co is defined as the depletion depth d of the metallic bonding phase. Using these definitions, the analysis depth D measured by the X-rays irradiated in the characteristic X-ray analysis, and the amount of Co mx actually measured by the characteristic X-ray analysis, an equation is created based on the conservation of mass of the amount of Co, and the following equation (1) is obtained.
[0026]
number
[0027] By solving equation (1) with respect to the depletion depth d, we obtain equation (2).
[0028]
number
[0029] Here, the concentration of the metallic bonding phase remaining between the hard particles must be estimated in advance using an analysis method attached to the scanning electron microscope, etc. The analysis depth is determined by the X-ray intensity of the characteristic X-ray analyzer used and the composition of the cemented carbide to be analyzed.
[0030] Characteristic X-ray analyzers include energy dispersive X-ray analyzers (EDS) and wavelength dispersive X-ray analyzers (WDS). Both instruments measure the chemical composition of a sample by detecting the characteristic X-rays emitted from the sample surface, with EDS measuring the energy of the characteristic X-rays and WDS measuring the wavelength of the characteristic X-rays.
[0031] In the EDS, the reaction region of the characteristic X-rays is relatively shallow at a depth of several μm, whereas the WDS has an analysis depth of more than 10 μm. In the present invention, considering that the material to be analyzed has hard particles with a diameter of about several μm, it can be said that a wavelength dispersive characteristic X-ray analyzer (WDS), which can measure the depth of multiple particles, is a more desirable analytical device.
[0032] Although the impoverishment depth has such a simplified definition, it is arithmetically uniquely determined and always intersects with the transition region of the Co amount, so it is a very easy definition to handle when stating it as a rule in specifications, etc. In addition, because this measurement method is non-destructive, it can be used directly for shipping inspection and can also be used for cause analysis when an abnormality occurs.
[0033] As described above, it is possible to calculate the depletion depth d of the metallic bonding phase from four pieces of information: the composition m1 of the cemented carbide base body, the composition mx measured from the top surface by characteristic X-ray analysis after the same base body is processed into a sliding electrode and the metallic bonding phase is selectively etched, the composition m2 of the metallic bonding phase that remains in small amounts between the hard particles in the depleted region of the selectively etched metallic bonding phase, and the analysis depth D measured by the emission of characteristic X-rays in characteristic X-ray analysis.
[0034] A flow chart of the above-described method for measuring the depletion depth of the surface metallic binder phase in a cemented carbide is shown in Fig. 5. By carrying out this process, even in a situation where the metallic binder phase of the cemented carbide is removed from the surface by etching, the metallic binder phase leaves the hard particle phase in a mesh-like shape and selective corrosion progresses in a tunnel-like shape, the calculated corrosion depth can nondestructively and unambiguously define the depth of the corrosion front, the boundary of which is actually ambiguous.
[0035] A comparison test between the calculated and measured values of the above-mentioned defect depth was carried out for three material types with different particle sizes (fine, medium, and coarse), by producing samples for each of the fine, medium, and coarse grains. The average particle size of each was 0.6 to 1.0 μm for fine grains, 2.0 to 4.0 μm for medium grains, and 5.0 μm or more for coarse grains. The actual measurement values were measured at several locations using a wavelength dispersive X-ray analyzer (WDS) and the average values were calculated.
[0036] As a result of the test, the difference between the calculated and measured values of the depletion depth was much smaller than half the particle diameter of the hard particles in all cases of fine, medium, and coarse particles. The value of half the particle diameter of the hard particles can be recognized as a boundary value that determines whether or not the hard particles will fall off, and if the difference between the calculated and measured values of the depletion depth exceeds half the particle diameter of the hard particles, it will have a negative effect on the function of parts and tools made of cemented carbide when selective corrosion is performed. However, according to the test results, the difference between the calculated value of the depletion depth and the measured value is much smaller than half the particle diameter of the hard particles, so it was confirmed that the calculation method of the depletion depth according to the present invention is extremely effective.
[0037] By using this technique, it is possible to selectively corrode only the metallic bonding phase on the surface of the cemented carbide that constitutes the sliding electrode, thereby creating a structure in which the metallic bonding phase does not come into direct contact with the conductive metal wire, and it is possible to accurately calculate the corrosion depth in a non-destructive manner.
[0038] The results of experiments carried out to verify the effects of the present invention will now be described. Specifically, discharge voltage withstand tests were conducted using the following variables as the type of cemented carbide used in the sliding electrode, the change in micro-roughness on the sliding electrode surface, and the distance from the sliding electrode surface when the metallic bonding phase, which is mainly responsible for the electrical conductivity of the cemented carbide, was selectively removed by etching treatment.
[0039] The experimental conditions are as follows. For the three varieties shown in Table 1, dielectric breakdown tests were conducted on two types of polished surface (#800 and lapped finish) and two types with and without selective corrosion.
[0040] [Table 1]
[0041] -Measure Ra under two finish conditions -Preferential corrosion depth is calculated from X-ray wavelength spectroscopy analysis Dielectric breakdown test conditions: Room temperature (20℃±15℃) - Room humidity (45-85%) -Dielectric strength evaluation method: A brass electrode with a 90° taper and a tip of R1 and a sliding electrode made of cemented carbide are placed with a gap of 0.05 mm between the tip of the brass electrode and the sliding surface of the sliding electrode made of cemented carbide. A voltage is applied and the voltage at the point when dielectric breakdown occurs between the electrodes is measured and evaluated as the dielectric strength.
[0042] Figure 6 shows images of the cemented carbide surface taken with a scanning electron microscope, (a) as polished and (b) after selective etching.
[0043] The test results are shown in Figures 7 and 8. Figure 7(a) shows data relating to the present invention, and Figure 7(b) shows data relating to a comparative example. Comparisons of sample numbers 1 and 7, 3 and 9, and 5 and 11 show that lapping the cemented carbide surface increases and stabilizes the withstand voltage of all three varieties compared to #800. Comparisons of sample numbers 1 and 2, 3 and 4, and 5 and 6 show that the selective corrosion of the metallic bonding phase has resulted in a significant improvement in the withstand voltage for those that underwent lapping. On the other hand, comparisons of sample numbers 7 and 8, 9 and 10, and 11 and 12 show that in cases where the initial surface is rough, such as #800, the effect of selective corrosion is not apparent.
[0044] From this, it was confirmed that it is important to keep the surface roughness of the cemented carbide surface at a level of 0.01 μm or less in terms of Ra, and that even more remarkable effects can be obtained by selectively corroding only the metallic bonding phase of the cemented carbide surface in that state.
[0045] Next, the results of tests on the amount of wear of the sliding electrode caused by selective etching of the cemented carbide surface will be described. Figure 9 shows a schematic diagram of the wear amount of the sliding electrode with and without selective etching treatment of the cemented carbide surface, as a cross-sectional area due to wear. As shown as the sliding electrodes in Figure 1, the sliding electrodes are arranged above and below the workpiece, and Figure 9(a) is for pattern 1 (P1), where the wear cross-sectional area when the upper sliding electrode has selective etching treatment (abbreviated as "upper with") is X, and the wear cross-sectional area when the lower sliding electrode has not selective etching treatment (abbreviated as "lower without") is Y. The cross-sectional area ratio for this is X / Y.
[0046] FIG. 9(b) is for pattern 2 (P2), in which the wear cross-sectional area when the upper sliding electrode is not subjected to selective corrosion treatment (abbreviated as "upper no") is 1.25X, and the wear cross-sectional area when the lower sliding electrode is subjected to selective corrosion treatment (abbreviated as "lower with") is 0.8Y. This assumes that the effect of selective corrosion treatment in reducing the amount of wear is reduced by 20%, so the cross-sectional area ratio in this case is 1.25X / 0.8Y=1.5625X / Y. With these settings, if the result (upper with / lower without)<(upper without / lower with) is obtained, it is considered that selective corrosion treatment is effective in reducing the amount of wear.
[0047] The test results on the wear cross-sectional area were carried out based on the above viewpoints and are shown in Figs. 10 and 11. In Figures 10 and 11, the case where the upper sliding electrode was selectively corroded (with upper) and the lower sliding electrode was not selectively corroded (with lower) is pattern 1 (P1). The case where the upper sliding electrode was not selectively corroded (with upper) and the lower sliding electrode was selectively corroded (with lower) is pattern 2 (P2). The conductive metal wire and sliding electrode were installed as shown in Figures 12(a) and (b), and the usage times were 15 hours and 100 hours.
[0048] The test results showed that the relationship was (upper yes / lower no) < (upper no / lower yes), which confirmed that the selective corrosion treatment was effective in reducing wear.
[0049] The contact state between the conductive metal wire and the sliding electrode in the above test is shown in Figure 12(a) and (b). [Industrial Applicability]
[0050] INDUSTRIAL APPLICABILITY The present invention can suppress the occurrence of wear during electric current machining, and therefore can be widely used as a manufacturing method for a sliding electrode of a conductive metal wire that can extend the life of the electrode. [Explanation of symbols]
[0051] 1 Sliding electrode 2 Power supply 3 Metal Conductor Wire 4 Smooth surface after polishing 5. Surface after selective etching of metal bonding phase 6 hard particles 7 Metallic bonded phase 8 Metallic bonding phase remaining in the hard particle adhesion area
Claims
1. A method for manufacturing a sliding electrode made of a cemented carbide containing a hard particle phase and a metallic bonding phase and used in wire electric discharge machining using a conductive metal wire, characterized in that in a final finishing step of a smoothing process before use, the cemented carbide surface is subjected to a lapping treatment, and only the metallic bonding phase on the surface of the cemented carbide is selectively etched, resulting in a structure in which the metallic bonding phase does not come into direct contact with the conductive metal wire.
2. 2. The method for producing a sliding electrode according to claim 1, wherein the surface roughness of the cemented carbide surface after the lapping is 0.01 [mu]m or less in terms of Ra.
3. 2. The method for manufacturing a sliding electrode according to claim 1, characterized in that the depletion depth of the metallic bonding phase when only the metallic bonding phase is selectively etched is calculated from four pieces of information: the composition of the cemented carbide base, the composition measured by characteristic X-ray analysis from the top surface after the cemented carbide base is processed into a sliding electrode and the metallic bonding phase is selectively etched, the composition of the metallic bonding phase remaining slightly between the hard particles in the depleted region of the selectively etched metallic bonding phase, and the analysis depth measured by emission of characteristic X-rays in the characteristic X-ray analysis.
Citation Information
Patent Citations
Method for forming hard coating layer achieving excellent chipping resistance in high speed tooth cutting work on surface of solid tooth cutting tool of cemented carbide alloy
JP2003266243A
Material for energization piece for wire-cut electric discharge machine, energization piece, and method for manufacturing the same
JP2003266248A
Wire guide and / or electrode member for wire-cut electric discharge machining
JP2005246540A
Nano-porous metal and production method therefor
JP2008184671A
Cemented carbide and cutting tool
JP2011099164A
